Pregação e cruzada: a conversão dos infiéis nos poemas de Ramon Llull (1232-1316) - Lemos, Tatyana Nunes (2010)
In the thirteenth century, Muslims were still a major problem for Christianity. With the failure of the Crusades – passagium generale to the medieval – a few new proposals appear for the confrontation with Islam, including the use of preaching. During this period, public controversies were common, both in Christianity and Islamism. The mendicant orders were a major force in this type of debate. In Majorca, a thinker also struggled with this problem, Ramon Llull (1232-1316). The Catalan has created a new method based on his apologetic Art – for him revealed directly by God. Even defending preaching as the main way to achieve the conversion of muslims, Llull also took the use of force. Reformulated the concept of crusade, putting it at the service of missions, but without giving up the constraint. The Majorcan has developed his ideas in various works. We will review some of his poems - sources still unexplored by mainstream scholars to the subject matter - to understand how Llull built your project apologetic.